In-situ synthesis of titania nanosheet – CdS nanoparticle composites by combined hydrothermal – selective adsorption and reaction for enhanced photocatalytic activity. (2021) - Manikkoth, Sindhu Thalappan; Thulasi, Kunnambeth M.; Palantavida, Shajesh; Kizhakkekilikoodayil Vijayan, Baiju
Abstract: Here we report an in-situ procedure for the synthesis of titania nanosheet (TNS) – CdS nanoparticle composite having excellent phototocatalytic activity. Two dimensional TNS were synthesized via hydrothermal treatment. The TNS is made composites with CdS by an adsorption and reaction in presence of triethanolamine. The characterizations were done by X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM) and diffuse reflectance spectroscopy (DRS). Photocatalytic performance was studied using methylene blue degradation and confirmed by coumarin fluorescence probe method. Different TNS/CdS composites with increasing Cd/Ti molar ratio (TNS/0.1CdS, TNS/0.5CdS & TNS/1CdS) were prepared and better result is achieved with TNS/0.5CdS.